2020
DOI: 10.1186/s42358-020-00155-3
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of MSU crystals injection and high fat-diet feeding on the establishment of a gout model in C57BL/6 mice

Abstract: Objective Gout is characterized by inflammatory arthritis with hyperuricaemia and deposition of monosodium urate (MSU) crystals in the joints. Several animal models have been proposed based on MSU crystals injection or high-fat diet feeding; however, neither hyperuricaemia model nor acute gout model can effectively reflect clinical features of gout. This study aimed to assess the effectiveness of a compound gout model induced by the combination of MSU crystals injection and high-fat diet feeding. Methods The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…Studies have shown that the gut microbiota is involved in the response to MSU crystals in a gout model of mice, whereas the germ-free mice or mice treated with antibiotics do not respond to the injections of MSU crystals ( Vieira et al, 2015 ). Based on the 16S rRNA sequencing ( Lin et al, 2020b ), the top three relatively dominant phyla of the mouse gut microbiota were Firmicutes, Bacteroidetes, and Proteobacteria. In our study, the relatively dominant phyla of the mouse gut microbiota were Firmicutes and Bacteroidetes, while the MSU crystals and HFD altered the composition of the gut microbiota mainly by decreasing the relative abundance of Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that the gut microbiota is involved in the response to MSU crystals in a gout model of mice, whereas the germ-free mice or mice treated with antibiotics do not respond to the injections of MSU crystals ( Vieira et al, 2015 ). Based on the 16S rRNA sequencing ( Lin et al, 2020b ), the top three relatively dominant phyla of the mouse gut microbiota were Firmicutes, Bacteroidetes, and Proteobacteria. In our study, the relatively dominant phyla of the mouse gut microbiota were Firmicutes and Bacteroidetes, while the MSU crystals and HFD altered the composition of the gut microbiota mainly by decreasing the relative abundance of Bacteroidetes.…”
Section: Discussionmentioning
confidence: 99%
“…Co., Ltd.) every day and were individually injected a total of 40 μl of phosphate buffered saline (PBS) into the right rear footpad once every 10 days. The other four groups of mice were fed daily with HFD (10% yeast extract) and were injected with MSU crystals (1 mg mixed in 40 μl PBS) into the right hind footpad once every 10 days ( Lin et al, 2020b ). The experiments lasted for 6 weeks after the mouse models of gouty arthritis were established.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…given the strong association between this disease and obesity (31,32). This issue has been recently explored in a gout mouse model following footpad injections of MSU crystals in animals which were simultaneously fed with a high fat diet (containing 10% yeast extracts, likely to be an w-6 Fatty acid-rich diet, low in w-3 Fatty acids) (33). Interestingly, this model reproduced the rise in inflammatory cytokines seen in patients during acute gout flares, as well as the intestinal dysbiosis (commonly associated with high PUFA diet) which is also a hallmark of the disease (34).…”
Section: Gout and Food Intake: Not Only Urate Not Only Inflammasome-dependentmentioning
confidence: 99%
“…The control group was fed with a standard diet, and 40 μL of PBS was injected into the right hind footpad every 10 days. The animals in the other three groups were fed with HFD (10% yeast extract) and injected with MSU crystals (1 mg MSU crystals in 40 μL PBS/mouse) every 10 days to simulate gouty arthritis (Lin et al, 2020). Six-week therapy started at the induction of the gouty arthritis model.…”
Section: Animals and Drug Administrationmentioning
confidence: 99%